Electrolyte system strategies for anionic isotachophoresis with electrospray‐ionization mass‐spectrometric detection. 2. Isotachophoresis in moving‐boundary systems. Issue 24 (31st October 2013) - Gebauer, Petr; Malá, Zdena; Boček, Petr
<x xml:space="preserve">Abstract</x> This contribution is the second part of the project on strategies used in the selection of electrolyte systems for anionic ITP with ESI‐mass spectrometric detection. It presents ITP as a powerful tool for selective stacking of anionic analytes, performed in a nonconventional way in moving‐boundary systems where two co‐anions are present in both the leading and terminating zones. The theoretical background is given to substantiate the conditions for the existence and migration of ITP boundaries in moving‐boundary systems and stacking of analytes at these boundaries. The practical aspects of the theory are shown in form of stacking‐window diagrams that bring immediate information about which analytes are stacked in a given system. The presented theory and strategy are illustrated and verified on the example of analysis of a model mixture of salicylic acid, ibuprofen and diclofenac, and comparison of regular and free‐acid ITP with moving‐boundary ITP systems formed by formic and propionic acids and ammonium as counterion.